MIEJSCE I PAMIĘĆ W PÓŹNEJ TWÓRCZOŚCI MARKA NOWAKOWSKIEGO. PROLEGOMENA - Kudyba, Wojciech (Colloquia Litteraria, 2016)
Since 1990s Marek Nowakowski has systematically expanded the sphere of memoir-writing prose, which he built himself. In this prose it is spatial elements that first and foremost evoke images of the past, and a flâneur often becomes narrator. Gazing at architectural and urbanistic changes, he gives himself to memoirs. Various gastronomic establishments, understood as places of freedom, are particularly important goals of his journey to the past. Nowakowski also eagerly mentions specific individuals as well as types of their professions, which allowed for independence from the totalitarian rule of the Polish People’s Republic.